'Lebanon is more than a nation, more than a country. It is a message.' Lebanon as a model of Christian–Muslim relations*. Issue 3 (2nd September 2017) - Hager, Anna
Abstract: Defining Lebanon as a model of Christian–Muslim relations seems surprising given its history of sectarian violence. This paper, however, investigates how, in recent years, key religious and political actors (the churches, official Islamic institutions, political parties, Hezbollah, Islamist movements) have attempted to establish Lebanon as a model for both Christian–Muslim relations and the Christian presence in the Middle-East. A historical and philological approach will question the idea that these discourses are merely symbolic, and instead display the motivations, the strategies and the limits in actually promoting interreligious relations.